Patagonian toothfish-inspired aluminum coordination hydrogel sensors for real-time rainfall monitoring - Xiaoyu Guan; Yanxia Zhu; Jianxun Luo; Xuechuan Wang; Hao Gong; Mohammed A Abosheasha; Bingyuan Zhang; Sai Zheng; Dongping Li; Qingxin Han; Motoki Ueda; Yoshihiro Ito (International Journal of Extreme Manufacturing)
Compared with traditional rain gauges and weather radars, hydrogel flexible electronic sensor capable of responding directly to rainfall events with promptness and authenticity, shows great prospects in real-time rainfall monitoring. Aluminum coordination hydrogel (Al-HG), one of the most qualified sensors suitable for rainfall monitoring, however, is currently impeded from widespread application by its weak mechanical properties due to the low binding strength between Al ^3+ and functional ligands. Herein, inspired by the antifreeze proteins (AFPs) that protect those Patagonian toothfishes by strongly binding to ice crystals at freezing temperatures, a low temperature-induced strategy is introduced to promote more and stronger ligand carboxyls firm combination with Al ^3+ , thus forming a high-coordinated structure to deal with this challenge. Expectedly, the whole mechanical performance of the product Al-HG _F1/F2 obtained by the low temperature-induced strategy is improved. For example, the tensile fracture toughness and the maximum compressive stress of Al-HG _F1/F2 are 1.66 MJ·m ^−3 and 12.01 MPa, approximately twice those of the sample Al-HG _F3/F0 obtained by traditional soaking method (0.86 MJ·m ^−3 and 7.38 MPa, respectively). Coupled with its good biocompatibility, ionic conductivity, and sensing ability, Al-HG _F1/F2 demonstrates promising application for real-time rainfall monitoring in discrepant rainfall intensities, different zones, and even under extreme environments. This work aims to offer a stride toward mechanically robust aluminum coordination hydrogel sensors for real-time rainfall monitoring as well as provide insights into flood prevention and disaster mitigation.